Dynamics and Endogeneity of Firms' Recruitment Behaviour - Felix Ehrenfried; Christian Holzner (Center for Economic Studies and ifo Institute (CESifo), 2018)
Models of random search, directed search, or stock-ow matching differ substantially in the way they assume that job seekers and firms behave during the recruitment process. In this paper we identify new patterns about the recruitment behaviour of firms using the entropy balancing technique and argue that stock-flow matching models - if suitably amended by a time-consuming screening technology - are best able to explain why the vacancy-filling hazard is increasing during the planned search period and decreases thereafter, why most applicants arrive early in the recruitment process, and why the willingness to pay higher wages or to hire less qualified or experienced applicants increases for firms, which have been unlucky and unable to hire until the intended starting date.
Keywords: J63; J64; 330; recruitment; planned search duration; stock-flow matching